An empirical investigation of the factors that influence the customer churn in the Portuguese fixed telecommunications industry: A survival analysis application - Portela, S.; Menezes, R. (Business Review, 2010)
Considering that profits from customer relationships are the lifeblood of firms (Grant and Schlesinger, 1995), an improvement on the customer management is essential to ensure the competitivity and success of firms, mainly in a period of economic recession. For the last decade, Portuguese customers of fixed telecommunications have easily switched the service provider, which has been very damaging for the business performance and, therefore, for the economy. This study aims to develop a comprehensive model of the residential customer churn in the fixed telecommunications industry in Portugal, which can support managers on the customer portfolio management. A survival analysis model is developed based on a random sample of 830 customers. Our results show that the majority of variables that influence customer churn are related to the customer spending with the service provider, and that usage, product or even subscription conditions do not seem to influence the duration of the relationship. We also found that the probability of a given active customer cancels his/ her relationship with the firm is neither constant over time nor across customers. Lastly, it seems that satisfaction does not influence customer churn. We can conclude that pricing is a sensitive area in this industry. The Portuguese market of fixed telecommunications (FT) soared in the last decade and, as a consequence, firms focused on customer acquisition and they neglected customer retention. Strong competition and low switching costs have given rise to a phenomenon of customer switching behaviour, and, thus, high customer churn rates, which has serious consequences for business performance and, therefore, for the economy. According to several researchers, customer churn (i.e., the customer’s decision to terminate the relationship with a provider) is the main reason of profitability losses in the telecommunications industry (TI), due to losses on current and potential revenues, marketing costs, and brand image (e.g., Ahn et al., 2006; Qian et al., 2006; Zhang et al., 2006). Nevertheless, firms must change their strategy from customer acquisition to the retention of potentially valuable customers (Hadden et al., 2005; Hung et al., 2006), because the market is becoming saturated and firms cannot lose valuable customers to their competitors, mainly in a period of economic recession. Bolton and Tarasi (2006) suggest that customer retention is often easier and cheaper than customer acquisition in stable markets.